Creative writing training as a therapeutic tool for individuals with bipolar disorder - Dheka Dwi Agustiningsih; H. Halimah; Dine Hasya Dwifa; Nisha Nurhanisa; Anggun Kurnia Likawati (Jurnal Abmas, 2026)
This community service is a collaborative activity carried out by the Indonesian Language and Literature Study Program, Universitas Pendidikan Indonesia, together with Rumah Kita (Komunitas Peduli Bipolar Indonesia). The purpose of this community service is to build synergy in human resource development by providing literacy support to people with bipolar disorder. This community service takes the form of training for Rumah Kita members. The training materials covered expressive writing and creative writing as therapy, creative writing guidelines, and illustration as a complement to journaling. The results of the activity showed that the participants were very enthusiastic about attending each session of this community service. The participants were actively involved in discussions and practices facilitated by the committee and each presenter. Based on pre-test and post-test measurements of participants' knowledge and awareness of “Writing Therapy sebagai Penyembuh” and “Menulis Kreatif sebagai Terapi Jiwa” assessed through 13 indicators, participants' average knowledge and ability increased after receiving training and lectures from resource persons. This shows that this community service activity had positive results for the participants.    Abstrak Pengabdian masyarakat ini sebagai kegiatan kolaboratif yang dilakukan oleh Program Studi Bahasa dan Sastra Indonesia, Universitas Pendidikan Indonesia bersama dengan Rumah Kita (Komunitas Peduli Bipolar Indonesia). Adapun tujuan pengabdian ini ialah membangun sinergi dalam pengembangan sumber daya manusia melalui dukungan literasi bagi orang dengan bipolar. Bentuk kegiatan pengabdian ini adalah pelatihan yang menyasar anggota Rumah Kita sebagai partisipannya. Adapun dalam pelatihan, materi yang disampaikan yaitu terkait menulis ekspresif dan menulis kreatif sebagai terapi, panduan menulis kreatif, dan pembuatan ilustrasi sebagai pelengkap journaling. Hasil kegiatan menunjukkan bahwa partisipan memiliki antusias yang sangat tinggi untuk mengikuti setiap sesi pematerian dalam pengabdian ini. Partisipan terlibat aktif dalam diskusi dan praktik yang difasilitasi oleh panitia dan setiap pemateri. Berdasarkan pengukuran (pretest) dan (posttest) mengenai pengetahuan dan kesadaran peserta mengenai “Writing Therapy sebagai Penyembuh” serta “Menulis Kreatif sebagai Terapi Jiwa” yang diukur melalui 13 indikator, rata-rata kemampuan dan pengetahuan peserta meningkat setelah diberikan pelatihan dan pematerian dari narasumber. Hal ini menunjukkan bahwa kegiatan pengabdian kepada masyarakat ini memberikan hasil positif bagi peserta. Kata Kunci: bipolar; menulis kreatif; pengabdian masyarakat; terapi menulis